The The Hidden Curriculum of Islamic Education on Social Media: An Analysis of Islamic Values in Digital Educational Content at Ma’had Aly Nurul Jadid: The Hidden Curriculum of Islamic Education on Social Media: An Analysis of Islamic Values in Digital Educational Content at Ma’had Aly Nurul Jadid - Sitti Maghfiroh Fawaid; Muhammad Kholil (IAIN Ambon, 2026)
Abstract: The development of social media as a digital educational space has given rise to the phenomenon of the hidden curriculum in Islamic Religious Education (IRE), where Islamic values are acquired not only through formal learning but also through interactions and digital educational content consumed by students at Ma’had Aly Nurul Jadid. This study aims to analyze the forms of the PAI hidden curriculum on social media, as well as to identify the Islamic values contained in digital educational content and their influence on the learning patterns of students. This study employs a qualitative approach using a case study design, with data collection techniques including observation, interviews, and documentation involving faculty members, musrif/musrifah, and students as research informants. The findings indicate that social media contributes to enhancing students’ active engagement in learning, strengthening information literacy skills, and fostering a shift in the learning paradigm from passive to active and collaborative. Furthermore, the hidden curriculum formed through social media also plays a role in the internalization of Islamic values such as responsibility, independence, critical thinking, and digital ethics. Thus, social media can serve as a strategic tool in the development of digital-based Islamic Education (PAI) that is relevant to educational needs in the modern era. Keywords: hidden curriculum, information literacy, social media, Islamic values, ma’had aly.